Tree rings of Terminalia catappa Linn. and climate variability in a tropical South American estuary - Bovi, Renata Cristina [UNESP]; Ortega_Rodriguez, Daigard Ricardo; Hornink, Bruna; Olmedo, Gabriela Morais; Assis-Pereira, Gabriel; Tomazello-Filho, Mario; Cooper, Miguel; Bernardino, Angelo Fraga; Ferreira, Tiago Osório (Elsevier, 2024)
Given the prevailing uncertainties surrounding regional climate variability in southeastern Brazil, it is necessary to explore proxy records. The present dendrochronological study investigates the climate variations in the Neotropical estuarine system of the Rio Doce basin based on tree-rings records of 40 trees of Terminalia catappa Linn. The study demonstrates that annual growth rings of the species record the variations in regional precipitation, streamflow of the Rio Doce basin and surface temperature of the south Atlantic ocean. The variation in the South Atlantic Ocean Dipole Index (SAODI) directly affects precipitation and indirectly influences growth ring increment. The strong synchrony among the trees highlights the marked effect of precipitation seasonality regulated by SAODI. The trees exhibit robust growth during the dry period when Rio Doce's rains and streamflow decrease, emphasizing the potential of this chronology for climate and hydrological monitoring. The chronology of T. catappa, despite being short, is the first to provide information on the climate variability of a South America estuary ecosystem. Future studies should verify the influences of precipitation and SAODI on the growth of long-lived species aiming climate reconstructions in the region.
Keywords: Climate teleconnections; Dendrochronology; Floodplain; Streamflow